Correction: Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties. (6th March 2020) - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini
Abstract : Correction for 'Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties' by Sourik Mondal et al., New J. Chem., 2017, 41, 14652–14658.